2020
DOI: 10.1182/blood-2020-139996
|View full text |Cite
|
Sign up to set email alerts
|

Co-Expression of JAK2-V617F and Calr-del52 In Vivo Enhances Myeloproliferative Phenotype in Mice and Does Not Influence Competitive Fitness of Hematopoietic Stem Cells

Abstract: Myeloproliferative neoplasms (MPNs) are a group of hematopoietic stem cell disorders driven by mutations that constitutively activate physiologic signal transduction pathways essential for hematopoiesis. The majority of patients with classical MPNs harbor mutations within the Janus activated kinase 2 (JAK2), calreticulin (CALR), or thrombopoietin receptor (MPL) genes. The occurrence of driver mutations among patients is mutually exclusive but rare double positive cases have been reported. Employment of targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The current report is the first to show a case with the co‐occurrence of JAK2 V617F and CALR mutations in the same clone. In mice, HSCs carrying the JAK2 V617F and CALR mutations developed more severe MPN constitutional symptoms such as splenomegaly, leukocytosis and thrombocytosis without bone marrow fibrosis, compared with single‐mutant mice 16 . That study also showed murine JAK2 / CALR double‐mutated HSCs did not have a competitive advantage in transplantation settings 16 .…”
Section: Mutation Calr+ Jak2 Wt Calr+ Jak2 V617f+mentioning
confidence: 82%
See 2 more Smart Citations
“…The current report is the first to show a case with the co‐occurrence of JAK2 V617F and CALR mutations in the same clone. In mice, HSCs carrying the JAK2 V617F and CALR mutations developed more severe MPN constitutional symptoms such as splenomegaly, leukocytosis and thrombocytosis without bone marrow fibrosis, compared with single‐mutant mice 16 . That study also showed murine JAK2 / CALR double‐mutated HSCs did not have a competitive advantage in transplantation settings 16 .…”
Section: Mutation Calr+ Jak2 Wt Calr+ Jak2 V617f+mentioning
confidence: 82%
“…In mice, HSCs carrying the JAK2 V617F and CALR mutations developed more severe MPN constitutional symptoms such as splenomegaly, leukocytosis and thrombocytosis without bone marrow fibrosis, compared with single-mutant mice. 16 That study also showed murine JAK2/CALR double-mutated HSCs did not have a competitive advantage in transplantation settings. 16 Interestingly, our case suggested that adding a JAK2 V617F mutation to the CALR-mutated HSC compartment occurred during the progression from ET to MF.…”
Section: Supporting Informationmentioning
confidence: 92%
See 1 more Smart Citation